Investigating the Association between Technological Innovations and Nursing Care: A Narrative Literature Review - Jabade, Mangesh; Nadaf, Husain (YCAB Publisher, 2025)
Background: The integration of technological innovations into nursing care has become increasingly prominent, fundamentally altering the dynamics of healthcare delivery and patient outcomes. Digital technologies are now at the forefront of modern nursing practice, offering both opportunities and challenges. Objective: This narrative review aims to explore the complex relationship between technological advancements and nursing care, with a particular focus on the implications for clinical practice, the associated ethical and operational challenges, and potential future directions in healthcare innovation. Methods: A comprehensive literature search was conducted using multiple databases including PubMed, CINAHL, ScienceDirect, IEEE Xplore, Google Scholar, the Cochrane Library, and ProQuest Nursing and Allied Health. These sources were selected to ensure the inclusion of peer-reviewed articles, interdisciplinary research, systematic reviews, and grey literature. The search covered publications from January 2010 to December 2024, capturing a wide spectrum of developments relevant to nursing and technological integration. This review synthesizes and critically evaluates existing evidence concerning the impact of technology on nursing practice, patient care outcomes, and health system performance. Results: The findings indicate that technological tools such as electronic medical orders, clinical decision support systems, and telehealth platforms significantly enhance care delivery by improving documentation, expanding service accessibility, and enabling early detection of health issues. Nevertheless, barriers remain, including technological inequities, privacy concerns, and resistance among practitioners. Conclusion: The study underscores the transformative potential of technology in nursing and emphasizes the importance of sustained investment in research, education, and interdisciplinary collaboration to maximize its benefits. Keywords: nursing care; technology; patient outcomes; digital innovation; technological advancement healthcare transformation